2017
DOI: 10.15766/mep_2374-8265.10616
|View full text |Cite
|
Sign up to set email alerts
|

A Complicated Opioid Overdose: A Simulation for Emergency Medicine Residents

Abstract: Introduction: Opioid abuse is a growing problem in the United States. As a result, emergency medicine physicians often use naloxone to reverse opioid overdoses. While normally a safe drug, one potential complication of the antidote's use is flash pulmonary edema. This simulation was created after a patient followed the clinical course described after an opioid overdose. Methods: This simulation utilized a highfidelity simulator to expose resident emergency medicine physicians to flash pulmonary edema secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Maddry et al showed that emergency medicine residents had greater long‐term knowledge retention in clinical toxicology after a SBME training compared to a traditional lecture 27 . Similarly, Keenan et al and Thomas et al showed that emergency residents had increased comfort with managing respectively an opioid and lithium overdose after a SBME training 28,29 . Combined with the results of our study, these findings suggest that SBME could provide a valuable addition to the teaching repertoire of CPT teachers, especially since an increasing number of medical schools already have simulation mannequins available.…”
Section: Discussionsupporting
confidence: 80%
“…Maddry et al showed that emergency medicine residents had greater long‐term knowledge retention in clinical toxicology after a SBME training compared to a traditional lecture 27 . Similarly, Keenan et al and Thomas et al showed that emergency residents had increased comfort with managing respectively an opioid and lithium overdose after a SBME training 28,29 . Combined with the results of our study, these findings suggest that SBME could provide a valuable addition to the teaching repertoire of CPT teachers, especially since an increasing number of medical schools already have simulation mannequins available.…”
Section: Discussionsupporting
confidence: 80%
“…However, very few curricula are focused on addressing opioid addiction in the ED setting, and none of the curricula published to date include detailed information about starting patients on buprenorphine. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…This workshop fills a unique gap in the available medical education curricula as it is associated with bystander naloxone distribution and can be accomplished in 15 minutes. A search of MedEdPORTAL using the keyword naloxone identified three unique publications: One includes naloxone training within a larger multiday substance use disorder training session for students, 11 another discusses an adverse event for pulmonary edema after naloxone administration, 12 and the third addresses indications for naloxone for inpatient opioid reversal. 13 While there is literature on the importance of naloxone training for medical trainees, 14 our curriculum is unique in that it is a standalone brief workshop whose primary focus is on naloxone education for health care providers.…”
Section: Introductionmentioning
confidence: 99%